2015
DOI: 10.1038/srep10248
|View full text |Cite
|
Sign up to set email alerts
|

JBP485 promotes tear and mucin secretion in ocular surface epithelia

Abstract: Dry eye syndrome (DES), a multifactorial disease of the tears and ocular surface, is one of the most common ocular disorders. Tear film contains ocular mucins and is essential for maintaining the homeostasis of the wet ocular surface. Since there are a limited number of clinical options for the treatment of DES, additional novel treatments are needed to improve the clinical results. In this study, we found that placental extract-derived dipeptide (JBP485) clearly promoted the expression and secretion of gel-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
0
17
0
2
Order By: Relevance
“…Our recent study showed that JBP485 promotes tear and mucin secretion in corneal and conjunctival cells 30 . Clinically, decreased secretion of tears sometimes makes corneal wound healing slow or intractable.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our recent study showed that JBP485 promotes tear and mucin secretion in corneal and conjunctival cells 30 . Clinically, decreased secretion of tears sometimes makes corneal wound healing slow or intractable.…”
Section: Discussionmentioning
confidence: 96%
“…Albino Japanese rabbits were obtained from Kitayama Laboratories (Kyoto, Japan) and were maintained under pathogen-free conditions in the barrier facility. In vivo rabbit models of corneal wound closure were created as previously described 30 . Rabbits were anaesthetised with an intramuscular injection of ketamine hydrochloride (60 mg/kg of body mass; Daiichi Sankyo Propharma, Tokyo, Japan) and xylazine (5 mg/kg; Bayer Medical, Tokyo Japan) as well as with oxybuprocaine eye drop (Santen pharmaceutical company, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to such a mechanism, innate immunity also plays a role in humans. Interestingly, JBP485 promoted the expression and secretion of mucin in the conjunctival epithelium [17]. Mucin plays an important role to preserve gastrointestinal mucosal barrier against bacterial penetration, and therefore it could be possible that JBP485 protects the DSS-induced damage of the mucosal epithelial barrier by promoting the expression and secretion of mucin.…”
Section: Discussionmentioning
confidence: 98%
“…Mucins are transmembrane glycoproteins that are detected at the apical surface of all mucosal epithelial cells. They can be further classified as (a) secreted gel-forming mucins and (b) membrane-bound mucins [19]. Membrane-bound mucins have a single transmembrane domain including a large glycosylated extracellular domain, a helical transmembrane domain and a short cytoplasmic tail, and these mucins are expressed in the apical cell membranes of the epithelium [20].…”
Section: Discussionmentioning
confidence: 99%